Foreign Students’ Intention towards a China’s Third Party Mobile and Online Payment Platform Based on Alipay - Aktortifan R. P. Zhou J. (International Journal of Informatics and Computation, 2019)
As the times progressed, so many features of smartphones that are developed by producers in manufactures. Hardware and software are fused to deliver comfort and increase the productivity of users’ smartphone. The example of software that can help users for a convenient transaction is Alipay and Wechat Pay, a China’s third-party mobile and online payment platform developed by Alibaba Group and Tencent respectively. This research aimed to observe ex-pats’ motives in the use of a Chinese third-party online payment platform with the sample was some foreign students in Nanjing as the Alipay users. Based on Unified Theory and Acceptance and Use of Technology (UTAUT) which consists four key constructs (effort expectancy, performance expectancy, social influence, and facilitating conditions), the results found that behavioral intentions were significantly carried out by effort expectancy, performance expectancy, and facilitating conditions, while social influence factors were found to be insignificant.